Pesona Style Bahasa Arab Sebagai Bahasa Al-Qur’an Dan Awal Mula Perkembangan Ilmu Balāghah - Daud Lintang (Sekolah Tinggi Agama Islam Nurul Iman Bogor, 2018)
This article discusses the style (uslūb) of Arabic in all aspects of linguistic in the Qur'an, it countais phonology, morphology, syntax and semantics. The presence of all these styles makes it more fascinating and always interesting to be studied and researched by scientists who love Arabic language and literature. This research, wants to prove that Arabic as an al-Qur'an language is unmatched in the world, and the highest value as the unifying language of the people. Becaused the position of the Arabic language is not only neat and beautifully structured in the grammatical, but also in each words and sentences to have an artifact that exceeds poetry, prose and even the poems, especially before the Qur'an was revealed. So, to be completed perfect understanding to the Qur’an have to understand his languange wisodm (uslūb al-hakīm) very well. Moreover, the position of balāgha as a peak study of Arabic becomes very important.